2002
DOI: 10.1021/bi025951z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of Annexin A1 Binding to Solid-Supported Membranes:  A QCM Study

Abstract: By means of the quartz crystal microbalance (QCM) technique, the interaction of annexin A1 with lipid membranes was quantified using solid-supported bilayers immobilized on gold electrodes deposited on 5 MHz quartz plates. Solid-supported lipid bilayers were composed of a first octanethiol monolayer chemisorbed on gold and a physisorbed phospholipid monolayer obtained from vesicle fusion. This experimental setup enabled us to determine for the first time rate constants and affinity constants of annexin A1 bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 55 publications
5
65
0
1
Order By: Relevance
“…As expected, A1-mβG exhibited higher K d values than A5-mβG. However, A1-mβG displayed lower K d values for cultured cells expressing phosphatidylserine than previously reported for A1 alone binding to immobilized lipid bilayers containing phosphatidylserine,~39 nM (Kastl et al, 2002); there are no previous reports of A1 dissociation constants for cultured cells. We have previously shown that annexin A5 fusion proteins will not bind to normal endothelial cell controls Krais et al, 2013), and we here extend this finding to A1 fusion proteins by demonstrating that A1-mβG and A5-mβG bind only to cells expressing phosphatidylserine in a calcium-dependent manner with no detectable specific binding to normal controls lacking the phosphatidylserine target.…”
Section: Discussionsupporting
confidence: 62%
“…As expected, A1-mβG exhibited higher K d values than A5-mβG. However, A1-mβG displayed lower K d values for cultured cells expressing phosphatidylserine than previously reported for A1 alone binding to immobilized lipid bilayers containing phosphatidylserine,~39 nM (Kastl et al, 2002); there are no previous reports of A1 dissociation constants for cultured cells. We have previously shown that annexin A5 fusion proteins will not bind to normal endothelial cell controls Krais et al, 2013), and we here extend this finding to A1 fusion proteins by demonstrating that A1-mβG and A5-mβG bind only to cells expressing phosphatidylserine in a calcium-dependent manner with no detectable specific binding to normal controls lacking the phosphatidylserine target.…”
Section: Discussionsupporting
confidence: 62%
“…Typical annexins carry 4 similar domains defined by 5 α-helices, and each domain contains a characteristic type 2 calcium-binding motif [GXGTD-[ X ] 37 -(D/E)]. Most of the evolutionarily conserved annexins can interact with PS [Kastl et al, 2002;Rosenbaum et al, 2011], and during skin injury they can bind at the site of tissue damage to suppress the binding and activation of coagulation factors at the cell surface but also promote repair [Bouter et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…It was adsorbed on a POPC:(palmitoyloleoylphosphatidylserine = POPS) (4:1) lipid monolayer assembled by vesicle fusion on an octanethiol monolayer tethered to the gold surface of a QCM. 91 Adsorption of annexin A1 to this hybrid bilayer in the presence of Ca 2+ ions was monitored by the decrease in resonance frequency. No adsorption was observed in the absence of Ca 2+ ions, nor even in their presence, if the POPC-POPS mixture was replaced by pure POPC.…”
Section: Alkanethiol-lipid Hybrid Bilayersmentioning
confidence: 99%